2004
DOI: 10.1042/bj20031601
|View full text |Cite
|
Sign up to set email alerts
|

Redox regulation of DNA binding activity of DREF (DNA replication-related element binding factor) in Drosophila

Abstract: DREF [DRE (DNA replication-related element) binding factor] is an 80 kDa polypeptide homodimer which plays an important role in regulating cell proliferation-related genes. Both DNA binding and dimer formation activities are associated with residues 16-115 of the N-terminal region. However, the mechanisms by which DREF dimerization and DNA binding are regulated remain unknown. Here, we report that the DNA binding activity of DREF is regulated by a redox mechanism, and that the cysteine residues are involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…In a recent study, we found that the DNA binding activity of DREF is directly modulated by elevated ROS through the effect of ROS on two cysteine residues located in the DNAbinding domain of DREF (36). One prediction of a functional relationship between DREF and catalase expression is that reducing catalase expression might suppress a phenotype associated with ectopic DREF over-expression.…”
Section: Catalase Amorphic Cat N1 Mutation Suppresses the Dref Over-expression-induced Rough Eye Phenotypementioning
confidence: 96%
“…In a recent study, we found that the DNA binding activity of DREF is directly modulated by elevated ROS through the effect of ROS on two cysteine residues located in the DNAbinding domain of DREF (36). One prediction of a functional relationship between DREF and catalase expression is that reducing catalase expression might suppress a phenotype associated with ectopic DREF over-expression.…”
Section: Catalase Amorphic Cat N1 Mutation Suppresses the Dref Over-expression-induced Rough Eye Phenotypementioning
confidence: 96%
“…Finally, the endogenous production of reactive oxygen species (ROS) as by-products of cellular metabolism can affect the REDOX status of replication factors and alter the initiation or progression of replication [ 24 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: The Multiple Causes Of the Replication Stressmentioning
confidence: 99%
“…Transfection of various DNA mixtures into Kc cells was performed using dimethyldioctadecyl ammonium bromide (DDAB) and the cells were harvested 48 h thereafter. The luciferase assay was carried out by means of a Luciferase Assay System (Promega), as previously described (Choi et al 2004). Luciferase activity was normalized with β-galactosidase activity to correct for transfection efficiency.…”
Section: Cell Culture and Dna Transfectionmentioning
confidence: 99%
“…DREF also modulates the transcription of the Drosophila mitochondrial transcription factor A (D-mtTFA) gene (Takata et al 2001), and the accessory subunit gene of Drosophila mitochondrial DNA polymerase . The DNA binding activity of DREF is regulated directly by elevated levels of ROS (Choi et al 2004), and this activity is modulated via the intracellular redox state . It was reported that ectopic DREF expression in Drosophila eye and wing imaginal disc cells induces both apoptosis and aberrant morphogenesis Yoshida et al 2001).…”
Section: Introductionmentioning
confidence: 99%